IDENTIFIKASI DAN UJI PATOGENISITAS CENDAWAN ENTOMOPATOGEN LOKAL TERHADAP Leptocorisa oratorius - Senewe, Emmy; Manengkey, Guntur (Universitas Sam Ratulangi, 2011)
ABSTRACT Leptocorisa oratorius is one major pest of rice in North Sulawesi. Hence, it is necessary to control the pest. The research objective was to identify and to test pathogenicity of local entomopathogen fungi which infected Leptocorisa oratorius. The pathogens were collected through sampling of L. oratorius which had been infected by the fungi in the field. The pathogenic fungi was isolated using PDA medium, identified followed by inoculation for pathogenecity test. During several sampling pest, it was found that L. oratorius was attacked by fungal pathogens in the field. The identification revelead that the fungal pathogens were Beauveria sp and Fusarium sp. Both the fungal pathogen produced white mycelium and could only be distinguished using microscope in the laboratory. Result of pathogenicity tests showed that the two fungal pathogens caused different mortality of the L. oratorius. Mortality of L. oratorius caused by pathogenic fungus Beauveria sp was 30.3% . Whereas, mortality of L. oratorius caused by Fusarium sp was only 3.33%. Keywords : pathogenic fungi, entomopathogen, pathogenicity tests, L. oratorius